Respon Suku Bunga Deposito dan Kredit Bank Umum terhadap Kebijakan Moneter Bank Indonesia - Septiani, Lisda; Imansyah, Muhammad Handry (PPJP ULM, 2023)
Many phenomena occur in International case studies, and various kinds of research show the relationship between interest rates (deposits and credits) and monetary policy carried out by Bank Indonesia. This type of research is quantitative research with secondary data taken from January 2010 to March 2021 (Time Series data), with two dependent variables: the first deposit interest rate and the second credit interest rate. There are three independent variables: BI Rate/BI7DRR, Economic Liquidity (M2), and Inflation. The analysis technique uses Multiple Linear Regression. The result is that the BI Rate/BI7DRR, Economic Liquidity, and Inflation together have a significant response/influence on deposit interest rates. Likewise, BI Rate/BI7DRR, Economic Liquidity, and Inflation have a practical response/impact on the credit interest rates at commercial banks.